Kod kreskowy DNA – praktyczne narzędzie taksonomii i inwentaryzacji entomofauny - Szyp-Borowska, Iwona; Sikora, Katarzyna (Leśne Prace Badawcze, 2019)
DNA barcoding is an innovative system designed to provide rapid, accurate, and automatable species identification by using short, standardized gene regions as internal species codes. The mitochondrial cytochrome C oxidase I (COI) gene was proposed by Paul Hebert as an official marker for animals, because of its small intraspecific but large interspecific variation. Since the launch of the project Barcode of Life, this simple technique has caught the interest of taxonomists, ecologists and plant-quarantine officers charged with the control of pests and invasive species. The great diversity of insects and their importance have made this group a major target for DNA barcoding. In most cases, the identification of insect species by traditional methods based on morphological features requires specialist knowledge and is labor-intensive. DNA barcoding aims at meeting the challenge of monitoring and documenting the biodiversity of insects. The utility of DNA barcoding for identifying small insects, cryptic taxa or rare species, as well as many species of forest entomofauna that are impossible to discriminate morphologically throughout all of their life stages, is a subject discussed in this review. Due to its usefulness, also in Poland in the Forestry Research Institute, a method for identifying selected species of saproxylic beetles based on the sequence of the COI region was developed. In the future, this method will be used to assess the state of biodiversity and the naturalness of forest ecosystems. Therefore, this and other future implications of this promising new technique are also discussed here.